Developing Students' Speaking Skills through Simulation Technique - Neysa AR Samaula; Mawardin Mawardin; Andi Patmasari; Anjar Kusuma Dewi (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The purpose of this study was to determine whether simulation technique can develop eighth grade students' speaking skills at SMP Negeri 2 Tanantovea. This study used quasi-experimental. The population of this study was 120 students. The sample of this study used cluster random sampling. The data collection of this study was pre-test and post-test. The data were collected through speaking tests, which consisted of pre-test and post-test, and analyzed using simple statistical methods. The result of pre-test in the experimental class was 1.1 and the control class was 1.13 and it means that the average score of the control class was higher than the experimental class while the post-test showed that the experimental class was 13.9 and the control class was 13.5. It means that the score in the experimental class was higher than the control class after using the treatment. It can be concluded that simulation technique significantly improved students' speaking skills and supported from the hypothesis. T-count was 46.2 and T-table was 1.67. It showed that, the null hypothesis was rejected and the alternative hypothesis was accepted. In conclusion, the use of simulation technique can significantly improve students' speaking skills at SMP Negeri Tanantovea Donggala.